1995
DOI: 10.1111/j.1476-5381.1995.tb17184.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural requirements at the melatonin receptor

Abstract: 1 High affinity, specific binding sites for the pineal hormone, melatonin (5-methoxy Nacetyltryptamine) can be detected in chick brain membranes by use of the radiolabelled agonist,2 The affinity of a number of analogues of melatonin at the 2-[1251I]-aMT binding site was determined and compared with an analysis of their electronic structure and significant quantitative relationships obtained. 3 The best correlations indicated that binding affinity was correlated with AE, the difference between the frontier orb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 39 publications
1
47
1
1
Order By: Relevance
“…Previous data indicated that the 5-methoxy group is a major determinant in the attachment of MLT to its receptors [18] and there is evidence that it can influence the intrinsic activity, even if there are a number of examples of agonists that do not have the methoxy group [22][23][24][25][26]. A more extensive investigation of the importance of the methoxy substituent for biological activity and selectivity toward human mt 1 and MT 2 receptors was investigated by deleting this group or by shifting it from C-5 to the other indole positions.…”
Section: Substituent Modification On the Indole Nucleusmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous data indicated that the 5-methoxy group is a major determinant in the attachment of MLT to its receptors [18] and there is evidence that it can influence the intrinsic activity, even if there are a number of examples of agonists that do not have the methoxy group [22][23][24][25][26]. A more extensive investigation of the importance of the methoxy substituent for biological activity and selectivity toward human mt 1 and MT 2 receptors was investigated by deleting this group or by shifting it from C-5 to the other indole positions.…”
Section: Substituent Modification On the Indole Nucleusmentioning
confidence: 99%
“…A number of molecular modeling studies of the MLT receptors have been reported [18,[29][30][31][32]. The level of sophistication of these models varies considerably as do the number and diversity of compounds on which they are based and on the building approach.…”
Section: Molecular Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…This product (I.a) also features in some QSAR expressions, such as those for melatonin analogues [44], thus indicating that dispersion forces could be involved in melatonin receptor binding. Furthermore, it is possible to make a reasonable estimate of the binding affinity between melatonin and its receptor based on the Williams et al [45] expression for the various components likely to be involved, with hydrogen bonding (see Table 3 for some typical values) making a significant contribution [46]. In contrast, a derivation for the binding energy of camphor to cytochrome P450 cam indicates that hydrophobic forces (desolvation) make the largest contribution [34].…”
Section: Appendix a Derivation Of Solvation And Desolvation Energiesmentioning
confidence: 99%
“…16) It has been stated that the 5-methoxy group in melatonin is involved in critical hydrogen bonding to the receptor recognition site. 28) If it is assumed that the methoxy group in compound 4 mimics the 5-methoxy group of melatonin, then transferring the amidoethyl group from C1 to C8 eliminated the steric interference between the amidoethyl group and the 2 substituent in compound 4 and resulted in an increase in binding affinity to both MT 1 and MT 2 receptors.…”
Section: Results and Conclusionmentioning
confidence: 99%